Insulin resistance, Ca2+ signaling alterations and vascular dysfunction in prediabetes and metabolic syndrome - Romero-García, Tatiana; Vázquez-Jiménez, J. Gustavo; Sánchez-Hernández, Rommel; Olivares-Reyes, J. Alberto; Rueda, Angélica (Frontiers in Physiology, 2025)
Prediabetes and Metabolic Syndrome (MetS) share a common pathway to induce vascular dysfunction through hyperinsulinemia without the presence of overt hyperglycemia. Insulin resistance (IR) is a key factor in vascular complications in diabetes; however, vascular dysfunction has been reported in MetS patients, even in the absence of chronic hyperglycemic conditions. We consider that the alterations in the intracellular Ca2+ handling of vascular smooth muscle cells (VSMCs) and the impairment of the insulin receptor signaling pathway may contribute to the etiology of vascular diseases in prediabetes and MetS. Therefore, it is critical to understand the mechanisms by which prediabetes and MetS alter the expression and activity of proteins involved in intracellular Ca2+ signaling in VSMCs, particularly those related to vasorelaxation. The functional unit, integrated by the voltage-gated L-type Ca2+ channel (CaV1.2), the Sarco/Endoplasmic Reticulum Ca2+ ATPase (SERCA pump), the ryanodine receptor (RyR), and the large-conductance Ca2+-activated K+ channel (BKCa), regulates the vascular tone and promotes vasorelaxation of the resistance arteries. Changes in this functional unit may contribute to vascular dysfunction. This review summarizes the most recent knowledge regarding alterations in the expression or activity of these proteins in the vasculature of experimental models with characteristics of prediabetes and MetS.